An integrated approach to the selection of municipal solid waste landfills through GIS, K-Means and multi-criteria decision analysis - Eghtesadifard, Mahmood; Afkhami, Payam; Bazyar, Arash (Environmental research, 2020)
Selecting the proper site for disposing of solid waste is one of the serious environmental and public health concerns in metropolises. This multifaceted issue encompasses environmental, economic, social, geographical, technical, and legal criteria. Some of these criteria, however, are less influenced by experts' subjective judgments because they display scientific specifications. This study drew on a novel, integrated method for the selection of municipal solid waste (MSW) landfills in the Iranian metropolis, Shiraz; the study relied on the GIS and multi-criteria decision-making methods, which helped to reduce the number of comparisons in collecting experts’ opinions, simplified the selection process, and enhanced the assessment method. The method proposed was regulated by DEMATEL and ANP. Primarily 13 criteria were identified in five groups through the Delphi method. Next, using the integrated method, the weight of each criterion was determined and was assigned to the corresponding layer in ArcGIS 10.5. By combining these layers through a fuzzy logic, the sites satisfying the disposal conditions were identified. The sites were then divided into six areas through the k-means clustering algorithm, while MOORA, WASPAS and COPRAS methods were used to discover the best sites based on their priorities. Finally, to confirm the reliability of the results, compare and verify them, and conduct sensitivity analysis on them, 13 scenarios were used. •Improving MSW disposal site selection through proposing a MCDA-GIS method.•Measuring dependencies between site selection criteria via dependency networks.•Discovering the candidate landfill sites using a fuzzy approach in ArcGIS 10.5.•Clustering the candidate sites via the k-means algorithm and ranking them.•Finding the best sites in the northeastern and southeastern zones of Shiraz.